English media texts, past and present : language and textual structure - Ungerer, Friedrich (Pragmatics & beyond, 2000)
This book is among the first to combine a historical view of media texts with a critical look at their textual diversity today. The thirteen chapters cover corpora of early news-papers and pamphlets, present-day news stories and commentaries, TV talk shows and commercials as well as internet presentations. The studies focus on the wide range of text types in 18th century newspapers and the interpersonal strategies of pamphlets; they pursue the development of the persuasive potential of headlines and advertisements right down to the sophisticated postmodernist and multilingual examples of today.